The Economic Impacts of Natural Disasters: A Review of Models and Empirical Studies. (25th June 2019) - Botzen, W J Wouter; Deschenes, Olivier; Sanders, Mark
Abstract: Economic losses from natural disasters have been increasing in recent decades. This has been attributed mainly to population and economic growth in disaster-prone areas. Future natural disaster losses are expected to increase due to a continued increase in economic exposure and climate change. This highlights the importance of designing policies that can mitigate the impacts of these disasters on the economy and society. A rapidly expanding literature has estimated the direct (e.g., property damage) and indirect (e.g., gross domestic product growth, trade) economic impacts of natural disasters. This article reviews this emerging literature. We synthesize the main theoretical, computational, and empirical methods used, summarize key findings on the economic impacts of natural disasters, and discuss factors that have been found to mitigate disaster impacts. We conclude by identifying lessons for policymakers and outlining an agenda for future research in this field.